FORMATION AND ACTIVITY OF COTTON GINNING FACTORIES IN THE SURKHANDARYA OKRUG (1925–1941) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the development of the cotton ginning industry in the Surkhandarya region between 1925 and 1941. The reconstruction of the Termiz cotton ginning plant, the construction of the Denov cotton ginning plant, and the establishment of new enterprises in the Khazarbog and Sherobod areas played an important role in expanding the cotton industry in the region. The study also analyzes the Soviet policy of expanding cotton cultivation, the improvement of raw cotton processing, modernization of technical equipment, and the expansion of the network of cotton procurement points. In addition, the article provides information about the activities of the cotton ginning industry and its economic significance on the eve of World War II and during its initial years.
Keywords: Surkhandarya region, cotton growing, cotton ginning industry, Termiz cotton ginning plant, Denov cotton plant, Khazarbog cotton plant, Sherobod cotton plant, Soviet period, cotton industry, collective farms, agriculture, cotton procurement trust.